Estrogen Deficiency Exacerbates Intervertebral Disc Degeneration Induced by Spinal Instability in Rats. Issue 9 (1st May 2019) - Liu, Qi; Wang, Xiaomeng; Hua, Yue; Kong, Ganggang; Wu, Xiuhua; Huang, Zhiping; Huang, Zucheng; Liu, Junhao; Yang, Zhou; Zhu, Qingan
Abstract : Study Design: An experimental animal study of osteoporosis (OP) and intervertebral disc degeneration (IDD). Objective: The aim of this study was to clarify the effects of estrogen deficiency and supplement on cervical IDD induced by bilateral facetectomy in rats. Summary of Background Data: The relationship between IDD and OP is still controversy with the wide prevalence in aged people. Methods: Seventy-two Sprague–Dawley female rats were randomly divided into ovariectomy (OVX) group, facet joints resection of C4-6 (FR), FR–OVX group, estrogen replacement therapy (ERT, based on the FR-OVX group) group, and sham group. Specimens of C4-6 segment were harvested at 12 and 24 weeks. The microstructures of C5 vertebrae, vertebral endplate lesions and calcification, and IDD of C5/6 disc were evaluated by micro-computed tomography (micro-CT) and histology. The protein and gene levels of aggrecan, Col2α1, matrix metalloprotease (MMP)-3, and MMP-13 in the C5/6 and C4/5 discs were measured. Results: Microstructures of C5 vertebral body were weakened significantly after ovariectomy, while restored effectively with estradiol supplementation. The facetectomy led to significant IDD, and the IDD was aggravated when combined with OVX. The IDD of the ERT group was alleviated effectively and similar to that of the FR group in intervertebral disc height, vertebral endplate lesions and calcification, and disc degeneration scores. In addition, the estrogen supplement maintained the extracellular matrix by decreasing MMP-3 and MMP-13, and increasing aggrecan and Col2α1 expression. Conclusion: The present study demonstrated that estrogen deficiency exacerbated IDD induced by spinal instability, while estrogen supplementation alleviated the progression of disc degeneration related to osteoporosis. Level of Evidence: N/A Abstract : Estrogen deficiency deteriorated vertebral bony microstructure and aggravated disc degeneration initialized by the bilateral facetectomy. While, estrogen supplementation effectively ameliorated the progression of disc degeneration, restored the vertebral microstructure, the disc height and vertebral endplate, as well as maintained the extracellular matrix homeostasis in the disc.